2021
DOI: 10.1590/1519-6984.227465
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Chagas disease in Southern Brazilian cardiac patients and their knowledge about the parasitosis and vectors

Abstract: Chagas disease (CD) is considered a typical low-income population sickness of the developing countries in Latin America. Given the historical relevance of CD in individuals in southern Rio Grande do Sul (RS) State, Brazil, the aim of this study was to identify the knowledge of the CD and its vectors by cardiac patients, and the prevalence of anti-T cruzi antibodies in these individuals in Pelotas, city located in Rio Grande do Sul (RS) state, Brazil. The subjects with cardiac disease were submitted to a semi-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Dutra et al . 26 carried out a study in patients with heart diseases who used the public assistance service provided by the Cardiology Outpatient Clinic that belongs to the UFPel, in Pelotas, RS State. These patients, who came from Cangucu, Herval, Pinheiro Machado and Piratini, counties in which CD was considered endemic in the 1980’s.…”
Section: Discussionmentioning
confidence: 99%
“…Dutra et al . 26 carried out a study in patients with heart diseases who used the public assistance service provided by the Cardiology Outpatient Clinic that belongs to the UFPel, in Pelotas, RS State. These patients, who came from Cangucu, Herval, Pinheiro Machado and Piratini, counties in which CD was considered endemic in the 1980’s.…”
Section: Discussionmentioning
confidence: 99%
“…It should be mentioned that a factor that may interfere with the number of captures of T. rubrovaria in RS is the population’s knowledge of vectors. A study showed that 45.3% of patients with cardiovascular diseases treated in Pelotas city, RS, were not capable of identifying triatomines 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Trypanosoma cruzi is the causative agent of Chagas disease or American trypanosomiasis, which infects about six to seven million people worldwide, mostly in Latin America (WHO, 2020;Bianchi et al, 2021), considered a typical disease of low-income population developing countries (Dutra et al, 2021). In fact, vectorborne transmission is limited to areas of South, Central and North Americas (Bern, 2015).…”
Section: Introductionmentioning
confidence: 99%